Relationship between demographic factors and learning styles of management undergraduates - Rajandran Peresamy .P,; Nanna Suryana,; Marthandan .G,; Md. Nor Hayati B. Tahir, (Penerbit Universiti Kebangsaan Malaysia, 2011)
The main objectives of this study are to identify learning style preferences and the relationship between demographic factors and learning styles among management undergraduates. The eight learning styles, that is, active, reflective, sensing, intuitive, visual, verbal, sequential, and global, as identified by Felder and Silverman (2002) were assessed to identify the learning style preferences of management undergraduates. Demographic variables, such as gender, ethnicity, entry qualification, field of study, type of institution and year of study, were tested to assess the relationships between these demographic factors and learning styles. The Index Learning Style (ILS) developed by Felder and Soloman (1991) was adapted and used as the survey instrument. Findings revealed that the dominant learning style preferences, in sequential order, are visual, sequential, reflective, sensing, global, active, intuitive, and verbal. Gender, ethnicity, entry qualifications, field of study, type of institution, and year of study were related to the learning styles of management undergraduates.